PERCEPTION OF LEGAL STUDENTS IN STATE ISLAMIC UNIVERSITY OF SULTAN MAULANA HASANUDDIN BANTEN ON ENGLISH FOR SPECIFIC PURPOSES: ENGLISH REQUIREMENT AND MATERIALS - Rohmawati, Cucum; Jannah, Dinda Luthfiatuul; Yuningsih, Yuningsih (Universitas Muhammadiyah Metro, 2025)
This research aims to determine the English proficiency requirements for students of the Sharia Faculty in the workplace and to ascertain the type of English materials that can be produced using the information gathered from the present investigation. This research was conducted at Maulana Hasanuddin Banten State Islamic University. The participants consisted of 50 students and 15 from the alumni. They represented faculty of Sharia Economic Law, Islamic, and Constitutional Law. Qualitative research was conducted using interview with open-ended questions was administered to gather data. Data analysis coding, data reduction, data display, and drawing conclusions or interpretations were applied to this study. The findings reveal that Sharia Faculty students require four English skills, including ESP materials on various topics. The highly desired speaking skill topics were conversation and and communication, as well as studies. Reading was necessary to understand the nuances of English in contracts, interpret English legal documents, examine Authentic Cases, conduct in-depth analyses of cases, and debate written judgments. Writing was needed for applying appropriate English in written letters of advice, understanding the fundamentals of English in contracts, and drafting legal regulations. Listening was needed to understand the client's issues and instructions before offering suggestions. Further research should be conducted to assess the effectiveness of the English materials developed based on this current study.